Is ulnar nerve decompression and anterior transposition effective on elbow range of motion in the treatment of cubital tunnel syndrome? Elbow range of motion in the treatment of cubital tunnel syndrome - korkmaz, ozgur; yildiray (Acta medica Medianae, 2021)
Aim of this study was to evaluate the clinical results and elbow range of motion of patients with cubital tunel syndrome who had undergone decompression and anterior ulnar nerve transposition. There were 11 patients 7 male and 4 female. Mean age of the patients were 45,45±16,22 years. The mean follow-up period of the patients was 14,81±6,98 months. Decompression and anterior transposition of the ulnar nerve were performed in all patients. Patients were classified according to McGowan-Goldberg classification system before surgery and in the last control after surgery. VAS scores, flexion and extension range of motion were evaluated before surgery and in the last control after surgery. 8 patients had stage 2A according to McGowan-Goldberg classification system and 3 patients had stage 2 B preoperatively. Postoperatively, 10 patients were stage 0 and one patient was stage 1. Preoperative mean VAS score was 8,45±0,93 and mean VAS score was 1,45±2,29 post operative. Pre operative mean elbow flexion extansion range of motion was 118,64°±11,42° and post operative mean elbow flexion extansion range of motion was 128,63°±7,77°. We found statistical significant difference between pre operative and post operative VAS values and elbow flexion extansion range of motion. Anterior subcutaneous ulnar nerve transposition is an effective surgical treatment method with increasing elbow range of motion in patients with cubital tunel syndrome.